Pemanfaatan Peta Kerawanan Longsor Kecamatan Suwawa Timur Sebagai Media Visual Pembelajaran Mitigasi Bencana Berdasarkan Analisis Modul Ajar dan Persepsi Guru Geografi - Merlin Merlin; Sri Maryati; Masruroh Masruroh (Universitas Negeri Gorontalo, 2026)
This study aims to analyze the feasibility of using the landslide hazard map of East Suwawa District as a visual learning tool for disaster mitigation in the Geography curriculum at State Senior High School 1 East Suwawa. The study employed a qualitative descriptive approach with data collection techniques including observation, interviews, documentation, and analysis of the Phase F Geography teaching module. The analysis examined the alignment of the map’s content with learning outcomes, learning objectives, disaster mitigation material, and classroom conditions at the school. The results indicate that disaster mitigation material is included in the Geography teaching module and is supported by the use of visual aids in the learning process. Based on the interview results, Geography teachers assessed that the landslide hazard map is relevant for use as a learning medium because it is capable of presenting spatial information directly related to the students’ surrounding environment. Additionally, the school has supporting facilities, such as an LCD screen and a projector, which enable the use of map media in learning activities. Thus, the landslide hazard map of East Suwawa Subdistrict is deemed suitable for use as a visual learning medium for disaster mitigation in the Geography subject.